Factor 5 Leiden Gene Mutation in Endometrium Cancer - Karataylı, Rengin; Özdemir, Suna; Çelik, Çetin; Balcı, Osman; Nergis, Süleyman; Acar, Hasan (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: In this study, our aim was to investigate the frequency of mutations on factor 5 Leiden gene (G1691A, A4070G, A5279G loci) in endometrial cancer patients. STUDY DESING: 216 patients who admitted to Selcuk University Meram Faculty of Medicine Obstetrics and Gynecology Department with similar complaints (such as postmenopausal bleeding and dysfunctional uterine bleeding) were included in the study. Patients were divided into 2 groups. In the 1st group, there were 105 endometrioid type endometrial adenocarcinoma patients and in the second group, there were 111 patients whose endometrial pathology reported as benign. Two groups are compared according to frequency of mutations on factor 5 Leiden gene (especially G1691A, A4070G, A5279G loci). RESULTS: There were not any statistically significant differences between groups according to frequency of mutations on factor 5 Leiden gene (p=0.743). CONCLUSION: There is no correlation between mutations of factor 5 Leiden gene with endometrial cancer